A structure-controllable silicon-aluminum composite aerogel material and preparation method thereof

By grinding fly ash and floating bead treatment, combining sol-gel method and specific dopants, a silicon-aluminum composite aerogel material with controllable structure is prepared, solving the utilization rate of silicon-aluminum in the prior art. The problem of low and unstable structural performance has achieved efficient and low-cost aerogel preparation and performance regulation.

CN118125459BActive Publication Date: 2025-02-25CHINESE RES ACAD OF ENVIRONMENTAL SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410304389.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-18
Publication Date
2025-02-25
Estimated Expiration
2044-03-18

AI Technical Summary

Technical Problem

In the prior art, when preparing silicon-aluminum composite aerogel from fly ash, the silicon-aluminum utilization rate is low, the steps are complicated, and the structural performance of the silicon-aluminum composite aerogel is unstable, so fine control cannot be achieved.

Method used

After using fly ash grinding and sieving, fly ash float beads are obtained by centrifugation, suction filtration and drying, and then soaked in hydrochloric acid to form a sol. After washing and dopant addition, silicon-aluminum composite is prepared by sol-gel method. The aerogel is soaked by multiple replacement of a mixed solution of silicate and ethanol, and finally obtains the aerogel material by solvent replacement of alcohol organic solvents.

Benefits of technology

Improve the utilization rate of silicon and aluminum and the stability of structural performance, realize the fine regulation of the structure and performance of silicon and aluminum composite aerogels, meet the diversified needs of aerogel structure in different fields, and simplify the process flow and reduce the The cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a structure-controllable silicon-aluminum composite aerogel material and a preparation method thereof, and belongs to the technical field of aerogel materials. The silicon-aluminum composite aerogel material of the present invention is prepared by a doped sol-gel method using fly ash floating beads and silicate containing Si-O structure as raw materials, ethanol as solvent, and supplemented with a specific dopant. The obtained silicon-aluminum composite aerogel material has good mechanical hardness, high porosity, low density, and large specific surface area. Compared with the conventional method of directly using fly ash as raw material alone, the method of the present invention not only greatly improves the content and utilization rate of silicon and aluminum in the raw material, but also overcomes the defect that the Al-Si ratio in the raw material cannot be effectively adjusted when fly ash is used as raw material alone, and can realize the fine regulation of the structure and performance of silicon-aluminum composite aerogel. The preparation process of the silicon-aluminum composite aerogel material of the present invention is relatively simple, low-cost, and can be industrially produced, which broadens the research ideas for the resource utilization of fly ash.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel materials, and in particular relates to a structure-controllable silicon-aluminum composite aerogel material and a preparation method thereof. Background Art

[0002] Combustion is the most direct way to obtain energy from coal. However, during the combustion of coal, a large amount of fly ash is produced. Among them, fly ash emitted by thermal power generation has become the largest source of industrial solid waste pollution. If fly ash is not properly handled, it will cause many harms to the environment and human health. For example, the amount of fly ash produced by coal combustion is relatively large, and its storage process will occupy a large amount of land; the particulate matter formed by fly ash in the atmosphere will promote the formation of haze; pollutants such as heavy metals contained in fly ash will enter and pollute the soil through the leaching process of rainwater. Therefore, it is necessary to carry out research on the comprehensive utilization of fly ash.

[0003] The main chemical components of fly ash are SiO2 and Al2O3 (accounting for about 50% to 90% of the total). In order to utilize the effective components, some researchers have prepared it into silica aerogel, alumina aerogel or silica-alumina composite aerogel. Aerogel is a highly dispersed solid material composed of colloidal particles that agglomerate to form a nanoporous network structure and fill the pores with a gaseous dispersion medium. Due to its unique characteristics such as ultra-low density, ultra-large specific surface area, ultra-low thermal conductivity, super strong adsorption performance and super strong thermal insulation performance, it is widely used in thermal insulation, adsorption separation, catalytic carrier and other fields. Different application fields have different requirements for aerogel structures: in the field of thermal insulation, the structure of aerogel needs to have a highly porous structure and low thermal conductivity to provide excellent thermal insulation performance; in the field of adsorption materials, the structure of aerogel needs to have a large specific surface area and uniform pore distribution to improve adsorption performance; in the field of catalyst carriers, the structure of aerogel needs to have a highly porous structure and a large specific surface area to improve the activity and stability of the catalyst; in the field of biomedicine, the structure of aerogel needs to have good biocompatibility and controllable pore structure for drug delivery, tissue engineering and other applications.

[0004] Chinese patents CN101717214A and CN107998996A disclose a method for preparing silicon-aluminum composite aerogel using fly ash as raw material. However, due to the fixed ratio of Al2O3 to SiO2 in the fly ash used, it is often impossible to achieve fine control of the structure of the silicon-aluminum composite aerogel, resulting in a small specific surface area, a large pore size, and unstable structural performance of the obtained silicon-aluminum composite aerogel, which cannot meet the diversified needs of aerogel structures in different fields; Chinese patent CN110668452A discloses a method for preparing silicon-aluminum composite aerogel from fly ash, which uses an alkali fusion-acid leaching process to extract silicon and aluminum components in the fly ash, and then uses a sol-gel method to synthesize silicon-aluminum composite aerogel, but this type of process has the disadvantages of low silicon and aluminum utilization rate and high raw material cost; Chinese patent CN116354373A uses a two-step leaching method of alkali fusion-water leaching-acid leaching to prepare silicon-aluminum composite aerogel from fly ash. Although it improves the total utilization rate of silicon and aluminum elements, the steps are relatively complicated. Summary of the invention

[0005] The purpose of the present invention is to provide a structure-controllable silicon-aluminum composite aerogel material and a preparation method thereof, so as to overcome the shortcomings of low silicon-aluminum utilization rate, complicated steps, unstable structure and performance of silicon-aluminum composite aerogel and inability to achieve fine control when preparing silicon-aluminum composite aerogel from fly ash in the prior art.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A method for preparing a structure-controllable silicon-aluminum composite aerogel comprises the following steps:

[0008] (1) Grinding and sieving fly ash, then pouring it into deionized water, centrifuging, filtering, and drying to obtain fly ash floating beads; the fly ash is fly ash containing more than 20% by mass of Al2O3 and more than 35% by mass of SiO2;

[0009] (2) Soak the fly ash beads in hydrochloric acid for 4 to 8 hours to obtain a sol, filter the sol and wash it with deionized water until it is neutral;

[0010] (3) placing the washed sol in a mixed solution of ethanol and water, stirring to dissolve, and then adding a dopant to obtain a gel;

[0011] (4) Immerse the gel in a mixed solution of silicate and anhydrous ethanol at 40-80°C in a water bath, replace the mixed solution of silicate and ethanol every 8-12 hours, and replace it 3-5 times;

[0012] (5) The soaked gel is subjected to solvent replacement with an alcohol organic solvent and then dried to obtain an aerogel material.

[0013] Furthermore, the specific process of step (1) is as follows: the fly ash is ground and passed through a 100-150 mesh sieve, poured into deionized water, stirred evenly, placed in a centrifuge and centrifuged at a speed of 5000-8000 rpm for 5-10 minutes, the upper suspension is filtered, and dried at 80-110° C. for 8-12 hours to obtain fly ash floating beads.

[0014] Furthermore, the concentration of the hydrochloric acid in step (2) is 1-4 mol / L, and each time the fly ash beads are soaked, 20-100 mL of hydrochloric acid is added for every 1 g of the fly ash beads.

[0015] Furthermore, in the mixed solution of ethanol and water in step (3), the volume ratio of ethanol to water is 1:(1-4), and during each immersion, the volume ratio of the gel to the mixed solution of ethanol and water is 1:(2-10).

[0016] Furthermore, the dopant in step (3) is a mixture of substance A and substance B, wherein substance A is propylene oxide or butylene oxide, and substance B is at least one of formamide, N,N-dimethylformamide or polyethylene glycol.

[0017] Furthermore, the amount of the dopant added in step (3) is 30-37 times the mass of the fly ash beads, wherein the mass ratio of substance A to substance B is 1:(1.6-2.5).

[0018] Furthermore, in the mixed solution of silicate and anhydrous ethanol in step (4), the volume ratio of silicate to anhydrous ethanol is (1-5):100, and the silicate is at least one of methyl orthosilicate or ethyl orthosilicate.

[0019] Furthermore, during the soaking in step (4), the volume ratio of the gel to the mixed solution of silicate and ethanol is 1:(2-10).

[0020] Furthermore, the alcohol organic solvent in step (5) is at least one of methanol, ethanol, isopropanol, acetone or tert-butanol.

[0021] Furthermore, the specific process of the solvent replacement in step (5) is: soaking the gel soaked in step (4) in an alcohol organic solvent, replacing the alcohol organic solvent every 8 to 12 hours, and replacing it three times.

[0022] Furthermore, the drying in step (5) is freeze drying or drying at normal pressure, wherein freeze drying is drying the gel after replacement of the alcohol organic solvent at -70 to -40°C for 24 to 36 hours; and normal pressure drying is drying the gel after replacement of the alcohol organic solvent at 50 to 70°C for 24 to 36 hours.

[0023] The present invention also provides a structure-controllable silicon-aluminum composite aerogel material prepared by the above method.

[0024] The beneficial effects of the present invention are:

[0025] The present invention uses fly ash floating beads and silicate containing Si-O structure as raw materials, ethanol as solvent, and a specific dopant to prepare a structure-controllable silicon-aluminum composite aerogel material through a doped sol-gel method. The obtained silicon-aluminum composite aerogel material has good mechanical hardness, high porosity, low density, and large specific surface area. Compared with the conventional method of directly using fly ash as raw material alone, the present invention first prepares it into fly ash floating beads, eliminating the loss of silicon and aluminum in the alkali melting-acid leaching process and other processes, greatly improving the content and utilization rate of silicon and aluminum in the raw material; then the fly ash floating beads are combined with the silicate containing Si-O structure as raw materials, and the silicon source content is adjusted in the sol-gel process, thereby overcoming the defect that the Al-Si ratio in the raw material cannot be effectively adjusted when fly ash is used as raw material alone, thereby achieving fine regulation of the structure and performance of the silicon-aluminum composite aerogel. In addition, the addition of specific dopants not only shortens the reaction process time by 6 to 8 hours, but also can further regulate the uniformity of the pore size and mechanical strength of the silicon-aluminum composite aerogel by adjusting the dosage of the dopant to meet the diverse needs of aerogel structures in different fields.

[0026] The aerogel material preparation process of the present invention is relatively simple, low-cost, and can be industrially produced, thus broadening the research ideas for fly ash resource utilization. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with the embodiments, but it should not be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the contents of the present invention above still fall within the scope of protection of the present invention.

[0028] Example 1

[0029] The fly ash from the coal-fired unit was ground and passed through a 100-mesh sieve. The mass percentages of Al2O3 and SiO2 in the fly ash were determined to be 20% and 35% respectively. The fly ash came from Unit 4 of Hebei Sanhe Power Plant.

[0030] The sieved fly ash is poured into deionized water and stirred. After stirring evenly, it is placed in a centrifuge and centrifuged at 5000 rpm for 5 minutes. The upper suspension is filtered and dried at 80°C for 12 hours to obtain fly ash floating beads.

[0031] Take 1g of the above floating beads and soak them in 20-100ml 1mol / L hydrochloric acid for 4 hours to obtain a sol, filter the sol and wash it with deionized water until it is neutral. Stir and dissolve the washed sol in a mixed solution of ethanol and water, wherein the ratio of ethanol to water in the mixed solution is 1:2, and then add 10g of propylene oxide and 20g of formamide as dopants to obtain a gel. At a water bath temperature of 60°C, soak the above gel in a mixed solution prepared by 5mL of methyl orthosilicate and 100mL of anhydrous ethanol, replace the ethyl orthosilicate / ethanol solution every 12h, and replace it three times. Solvent replace the soaked gel with tert-butanol, replace the tert-butanol every 12h, and replace it three times in total. Dry the above colloid at 60°C under normal pressure for 32h to obtain a fly ash aerogel material.

[0032] Example 2

[0033] The fly ash from the coal-fired unit was ground and passed through a 150-mesh sieve. The mass percentages of Al2O3 and SiO2 in the fly ash were determined to be 35% and 45% respectively. The fly ash came from Unit 1 of Hebei Sanhe Power Plant.

[0034] The sieved fly ash is poured into deionized water and stirred. After stirring evenly, it is placed in a centrifuge and centrifuged at 8000 rpm for 5 minutes. The upper suspension is filtered and dried at 80°C for 12 hours to obtain fly ash floating beads.

[0035] Take 1g of the above floating beads and soak them in 20-100ml 4mol / L hydrochloric acid for 4 hours to obtain a sol, filter the sol and wash it with deionized water until it is neutral. Stir and dissolve the washed sol in a mixed solution of ethanol and water, wherein the ratio of ethanol to water in the mixed solution is 1:4, and then add 12g of butylene oxide and 25g of polyethylene glycol as dopants to obtain a gel. At a water bath temperature of 60°C, soak the above gel in a mixed solution prepared by 1mL of tetraethyl orthosilicate and 100mL of anhydrous ethanol, replace the tetraethyl orthosilicate / ethanol solution every 12h, and replace it three times. Solvent replace the soaked gel with methanol, replace the methanol every 8h, and replace it three times in total. Dry the above colloid at -70°C for 24h to obtain a fly ash aerogel material.

[0036] Example 3

[0037] The fly ash from the coal-fired unit was ground and passed through a 100-mesh sieve. The mass percentages of Al2O3 and SiO2 in the fly ash were determined to be 35% and 40% respectively. The fly ash came from Unit 2 of Hebei Sanhe Power Plant.

[0038] The sieved fly ash is poured into deionized water and stirred. After stirring evenly, it is placed in a centrifuge and centrifuged at 5000 rpm for 10 minutes. The upper suspension is filtered and dried at 110°C for 8 hours to obtain fly ash floating beads.

[0039] Take 1g of the above floating beads and soak them in 20-100ml 2mol / L hydrochloric acid for 4 hours to obtain a sol, filter the sol and wash it with deionized water until it is neutral. Stir and dissolve the washed sol in a mixed solution of ethanol and water, wherein the ratio of ethanol to water in the mixed solution is 1:1, and then add 10g of propylene oxide and 25g of N,N-dimethylformamide as dopants to obtain a gel. At a water bath temperature of 60°C, soak the above gel in a mixed solution prepared by 2mL of tetraethyl orthosilicate and 100mL of anhydrous ethanol, and replace the tetraethyl orthosilicate / ethanol solution every 12h for three times. Solvent replace the soaked gel with isopropanol, replace the isopropanol every 12h for a total of three times, and freeze-dry the above colloid at -40°C for 36h to obtain a fly ash aerogel material.

[0040] Example 4

[0041] The preparation method is the same as that of Example 3, except that after the gel is obtained, the mixed solution used to soak the gel is a mixed solution prepared by 5 mL of ethyl orthosilicate and 100 mL of anhydrous ethanol.

[0042] Example 5

[0043] The preparation method is the same as that of Example 3, except that the final drying is performed by normal pressure drying.

[0044] Comparative Example 1

[0045] The fly ash from the coal-fired unit was ground and passed through a 100-mesh sieve. The mass percentages of Al2O3 and SiO2 in the fly ash were determined to be 35% and 40% respectively. The fly ash came from Unit 2 of Hebei Sanhe Power Plant.

[0046] Take 1g of the above fly ash and soak it in 20-100ml 2mol / L hydrochloric acid for 4 hours to obtain a sol, filter the sol and wash it with deionized water until it is neutral. Stir and dissolve the washed sol in a mixed solution of ethanol and water, wherein the ratio of ethanol to water in the mixed solution is 1:1, and then add 12g of propylene oxide and 25g of N,N-dimethylformamide as dopants to obtain a gel. At a water bath temperature of 60°C, soak the above gel in a mixed solution prepared by 2mL of tetraethyl orthosilicate and 100mL of anhydrous ethanol, and replace the tetraethyl orthosilicate / ethanol solution every 12h for three times. Solvent replace the soaked gel with isopropanol, replace the isopropanol every 12h for a total of three times, and dry the above colloid at -40°C for 36h to obtain a fly ash aerogel material.

[0047] Comparative Example 2

[0048] The preparation method is the same as that of Example 3, except that after the gel is obtained, the solution used to soak the gel is 100 mL of anhydrous ethanol solution.

[0049] Comparative Example 3

[0050] The preparation method is the same as that of Example 3, except that after the gel is obtained, the mixed solution used to soak the gel is a mixed solution prepared by 0.5 mL of ethyl orthosilicate and 100 mL of anhydrous ethanol.

[0051] Comparative Example 4

[0052] The preparation method is the same as that of Example 3, except that after the gel is obtained, the mixed solution used to soak the gel is a mixed solution prepared by 10 mL of ethyl orthosilicate and 100 mL of anhydrous ethanol.

[0053] Comparative Example 5

[0054] The preparation method is the same as that of Example 3, except that the doping agents used are 6 g of propylene oxide and 18 g of N,N-dimethylformamide.

[0055] Comparative Example 6

[0056] The preparation method is the same as that of Example 3, except that no dopant is added.

[0057] Comparative Example 7

[0058] The preparation method is the same as that of Example 3, except that only 10 g of propylene oxide is added as a dopant.

[0059] Comparative Example 8

[0060] The preparation method is the same as that of Example 3, except that only 25 g of N,N-dimethylformamide is added as a dopant.

[0061] Table 1 Performance parameters of fly ash aerogel materials prepared in various examples

[0062]

[0063] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. A person skilled in the art may modify or replace the technical solutions of the present invention with equivalents. The protection scope of the present invention shall be subject to the claims.

Claims

1. A method for preparing a structure-controllable silicon-aluminum composite aerogel, characterized in that: The following steps are involved: (1) Grinding and sieving fly ash, then pouring it into deionized water, centrifuging, filtering, and drying to obtain fly ash floating beads; the fly ash is fly ash containing more than 20% by mass of Al2O3 and more than 35% by mass of SiO2; (2) Soaking the fly ash beads in hydrochloric acid for 4 to 8 hours to obtain a sol, filtering the sol and washing it with deionized water until it is neutral; the concentration of the hydrochloric acid is 1 to 4 mol / L; (3) placing the washed sol in a mixed solution of ethanol and water, stirring to dissolve, and then adding a dopant to obtain a gel; (4) Immersing the gel in a mixed solution of silicate and anhydrous ethanol at 40-80° C. in a water bath, replacing the mixed solution of silicate and ethanol every 8-12 hours for 3-5 times; wherein the volume ratio of silicate to anhydrous ethanol in the mixed solution of silicate and anhydrous ethanol is (1-5):100, and the silicate is at least one of methyl orthosilicate or ethyl orthosilicate; and the volume ratio of the gel to the mixed solution of silicate and anhydrous ethanol is 1:(2-10); (5) The soaked gel is subjected to solvent replacement with an alcohol organic solvent and then dried to obtain an aerogel material.

2. The method according to claim 1, characterized in that The specific process of step (1) is as follows: the fly ash is ground and passed through a 100-150 mesh sieve, poured into deionized water, stirred evenly, placed in a centrifuge and centrifuged at a speed of 5000-8000 rpm for 5-10 minutes, the upper suspension is filtered, and dried at 80-110° C. for 8-12 hours to obtain fly ash floating beads.

3. The method according to claim 1, characterized in that In the mixed solution of ethanol and water in step (3), the volume ratio of ethanol to water is 1:(1-4).

4. The method according to claim 1, characterized in that: The dopant in step (3) is a mixture of substance A and substance B, wherein substance A is propylene oxide or butylene oxide, and substance B is at least one of formamide, N,N-dimethylformamide or polyethylene glycol.

5. The method according to claim 1, characterized in that The amount of the dopant added in step (3) is 30-37 times the mass of the fly ash beads, wherein the mass ratio of substance A to substance B is 1:(1.6-2.5).

6. The method according to claim 1, characterized in that The alcohol organic solvent in step (5) is at least one of methanol, ethanol, isopropanol or tert-butanol.

7. A structure-controllable silicon-aluminum composite aerogel material, characterized in that: The method is prepared by any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for preparing silicon-aluminum aerogel by using fly ash as raw material through normal pressure drying

    CN101717214A

  • Preparation method of silicon-aluminum composite aerogel powder

    CN107998996A

  • Method for preparing SiO2-Al2O3 composite aerogel material from fly ash

    CN110668452A

  • Method for preparing silicon-aluminum composite aerogel from fly ash based on two-step leaching method

    CN116354373A

  • Method for preparing Al2O3-SiO2 aerogel

    CN104591193A